Analisis Efektivitas OKR vs KPI dalam Manajemen Kinerja Industri - Jopinus Saragih; Margono; Idayanti Adelina Silalahi (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study examines the effectiveness and comparison between Key Performance Indicators (KPI) and Objectives and Key Results (OKR) in performance management within industrial companies. KPI focuses on measuring operational outcomes that are quantifiable and generally stable for routine monitoring, whereas OKR emphasizes ambitious objectives assessed through key results within relatively short cycles, thereby encouraging innovation and faster adaptation to market changes. Using a qualitative approach with a literature review method, the research analyzes differences in focus, structure, time horizon, flexibility, and cross-functional implementation. The findings indicate that KPI is effective for ensuring consistent operational performance and supporting systematic identification of improvement areas, while OKR is more effective in building transparency, engagement, and cross-department collaboration to integrate strategic goals. In conclusion, KPI and OKR are complementary; selecting the most suitable approach should consider industry needs and organizational culture, and combining both can provide a comprehensive view of performance—from operational stability to strategic adaptability.